Recruitment and Retention of Public Sector Teachers in Ghana: A Discrete Choice Experiment - Gad, B. K. (University of Ghana, 2015)
The shortage of public sector teachers in rural areas is one of the main challenges facing policy makers in the education sector, in both developing and developed countries. This study sought to analyze the preferences of teachers, and how they would respond to alternative incentives associated with working in a rural location. Discrete Choice Experiment (DCE) which is rooted in Random Utility Theory (RUT) was used to capture the responses of 120 teacher trainees in Berekum College of Education. However, the full and the subgroup models were generated using the binary probit in STATA (Version 11.0). Marginal effect was also estimated. The magnitude of estimates from both the probit model and the marginal effects indicate that, for rural area posting, teachers in the public sector generally prefer and place higher priority on incentive packages such as granting of study leave with pay, provision of housing and promotion after three years of work. This was generally supported by the subgroup analysis. Also, the levels of salary will be traded off for non-financial incentive packages. It is recommended that in order to desist from force recruitment and the problem of mitigating geographical imbalances of public sector teachers, policy makers in the education sector should adopt a strategy by granting of study leave with pay, provision of housing and promotion after three years of teaching in rural areas

Education Sector Performance Report - Ministry of Education, Ghana (Ministry of Education (Ghana), 2015)

One Laptop Per Child Policy in Ghana: Any Impact on Teaching and Learning? - Asante, Edward; Owusu-Ansah, Samuel (Library Philosophy and Practice (e-journal), 2015)
Keywords: ⛔ No DOI found

Using Unified Theory of Acceptance and Use of Technology Model to Predict Students' Behavioral Intention to Adopt and Use E-Counseling in Ghana - Kolog, Emmanuel Awuni; Sutinen, Erkki; Vanhalakka-Ruoho, Marjatta; Suhonen, Jarkko; Anohah, Ebenezer (International Journal of Modern Education and Computer Science, 2015)
The urge to progressively motivate e-counseling in schools is somewhat dependent on students' behavioral intention towards the use of counseling technologies. This paper presents an empirical approach of using Unified Theory of Acceptance and Use of Technology model to ascertain students' behavioral intention to adopt and use e-counseling in Ghana. Questionnaires were used to collect data from two hundred and fifty (N=250) randomly selected students from Ghana. Cronbach alpha (α) was first employed to validate and ascertain the reliability of the data. Subsequently, Multiple Linear Regression (MLR) was performed in analysing the data. After that, a follow-up interview was conducted to explore the variance in our findings from the collected data through the questionnaires. In the end, the reliability of the test items contained in the questionnaire yielded strongly at 87.6 %. Also, whereas the outcome of the research suggests Performance Expectancy (PE) (B = .511 , p= .000) and Social Influence (SI) (B = .165 p = .001) as the influencing constructs (factors) towards students' behavioral intention to adopt and use e-counseling, Facilitation Condition (FC) (B= .014, p= .723) and Effort Expectancy (EE) (B= .086 p= .080) had no significant effect on the behavioral intention of students to adopt and use e-counseling in Ghana.
Keywords: Counseling; E-Counseling; ICT; Unified Theory of Acceptance; Use of Technology (UTAUT)

ICT in Education Policy - Ghana - Ministry of Education, Ghana (Ministry of Education Ghana, 2015)

Learning and teaching with mobile devices: an approach in higher secondary education in Ghana - Grimus, Margarete; Ebner, Martin (International Journal of Mobile and Blended Learning, 2015)
While many developing nations find Internet-based e-learning unsuitable for their needs mobile learning methods--specifically those involving the use of mobile-phones for both formal and informal learning--hold great promise for them (Grimus et al, 2013b). In this paper chances and challenges introduced by mobile devices to support improvement and transformation of education in a Senior High School in Ghana are examined. The field-study draws attention to the local situation, looking at infrastructure and teachers and students attitudes in using digital learning material. This paper presents results of a pilot project at a Senior High Technical School in Ghana, by addressing the issue how mobile devices can be integrated in learning and teaching. Based on our results we conclude that teachers and students hold great promise for using mobile devices for learning. Together they developed content based on the national curriculum, available for eReaders and mobile phones.
Keywords: ERIC, Current Index to Journals in Education (CIJE); Educational Technology; Faculty Development; Feedback (Response); Foreign Countries; Ghana; Handheld Devices; Online Surveys; Secondary Education; Semi Structured Interviews; Student Attitudes; Teacher Attitudes; Technical Education; Technology Uses in Education; Telecommunications; Workshops; __:import:03; __:match:final; __:matched; __:study_id:2096257; ___working_potential_duplicate; __finaldtb

Learning and teaching with mobile devices: an approach in higher secondary education in Ghana - Grimus, Margarete; Ebner, Martin (International Journal of Mobile and Blended Learning, 2015)
While many developing nations find Internet-based e-learning unsuitable for their needs mobile learning methods--specifically those involving the use of mobile-phones for both formal and informal learning--hold great promise for them (Grimus et al, 2013b). In this paper chances and challenges introduced by mobile devices to support improvement and transformation of education in a Senior High School in Ghana are examined. The field-study draws attention to the local situation, looking at infrastructure and teachers and students attitudes in using digital learning material. This paper presents results of a pilot project at a Senior High Technical School in Ghana, by addressing the issue how mobile devices can be integrated in learning and teaching. Based on our results we conclude that teachers and students hold great promise for using mobile devices for learning. Together they developed content based on the national curriculum, available for eReaders and mobile phones.
Keywords: ERIC, Current Index to Journals in Education (CIJE); Educational Technology; Faculty Development; Feedback (Response); Foreign Countries; Ghana; Handheld Devices; Online Surveys; Secondary Education; Semi Structured Interviews; Student Attitudes; Teacher Attitudes; Technical Education; Technology Uses in Education; Telecommunications; Workshops; __:import:03; __:match:final; __:matched; __:study_id:2096257; ___working_potential_duplicate; __finaldtb

Basic school leaders in Ghana: how equipped are they? - Donkor, Anthony Kudjo (International Journal of Leadership in Education, 2015)

ICT in Education Policy - Ministry of Education, Ghana (2015)

E-Learning as a Vehicle for the Development of Rural Girls in Ghana, West Africa - Roberts-Lewis, Kristie; Orok, Michael E. (Information Communication Technology (ICT) Integration to Educational Curricula: A New Direction for Africa, 2015)
Keywords: Equity through Access; ⛔ No DOI found

The Use of Information and Communication Technology (ICT) for Knowledge Management in the Second Cycle Educational Institutions in Ghana - Ohemeng, Patrick; Twum, Edward; Nii, Isadore (International Journal of Computer Applications, 2015)
Given its capabilities to widen access, improve the quality and reduce the cost of developing, accessing and maintaining information, Information and Communication Technology (ICT) offers increased possibilities for managing knowledge. This paper thus investigates the level of utilization of ICT in the knowledge management processes in the Ghanaian educational system. Being a descriptive study, a randomly selected sample of second cycle educational institutions was surveyed through questionnaire. Using descriptive data analysis, the study found a low level of Information and Communication Technologies usage in knowledge management processes in the second cycle educational system. Knowledge management practices were found to be inefficient due to, among other things, absence of strategic policies and nonutilization of ICT. The findings indicate that the Secondary Schools are not deriving the efficiency returns of the computers they have acquired due to the absence of a deliberate and effective strategy for knowledge management. Also students, teachers and administrators in the second cycle schools are not benefitting from the information revolution for knowledge management. It was recommended that capacity building in knowledge management and improvement of Internet speed should be given priority attention by educational authorities.

Learning and Teaching With Mobile Devices: An Approach in Higher Secondary Education in Ghana - Grimus, Margarete; Ebner, Martin (International Journal of Mobile and Blended Learning, 2015)
While many developing nations find Internet-based e-learning unsuitable for their needs mobile learning methods – specifically those involving the use of mobile-phones for both formal and informal learning – hold great promise for them (Grimus et al, 2013b). In this paper chances and challenges introduced by mobile devices to support improvement and transformation of education in a Senior High School in Ghana are examined. The field-study draws attention to the local situation, looking at infrastructure and teachers and students attitudes in using digital learning material. This paper presents results of a pilot project at a Senior High Technical School in Ghana, by addressing the issue how mobile devices can be integrated in learning and teaching. Based on our results we conclude that teachers and students hold great promise for using mobile devices for learning. Together they developed content based on the national curriculum, available for eReaders and mobile phones.
Keywords: ___working_potential_duplicate

Factors determining digital divide in Ghana's basic schools - Quaicoe, James Sunney; Pata, Kai (2015 IST-Africa Conference, 2015)
This paper explores the concept of digital divide (DD) in Ghana’s basic schools in Sekondi-Takoradi Metropolis in Western Region. We tested the ICT culture variables as well as school location factor in respect to school’s digital divide. A survey sample contained 17 regional city schools from three different locations – central city in the region, towns away from the central city, and village schools. The survey instrument was developed with ten ICT culture variables. The variables in the instrument met the Cronbach’s Alpha threshold value of α = 0.70. Data was analysed with Descriptive statistics, Hierarchical Cluster analysis, Independent t-test, and Canonical discriminant analysis. We found that school location did not determine the schools DD, nonetheless the schools were digitally divided, – 2 clusters were found among schools. This DD was determined by certain ICT culture variables: Teacher’s ICT competences and the usage of ICT in Teacher’s professional practice were paramount.

Evaluating Teachers' Professional Development For ICT Use: Towards Innovative Classroom Practices - Agyei, D. D (International Journal of Education, 2015)
This paper describes an evaluation study designed to investigate the impact of an ICT-Instructional digital innovation in teaching Mathematics, English and Integrated Science subjects from the teacher capacity building professional development programme to classroom implementation at senior high school levels in Ghana. Interviews and survey data were used for data collection following a week professional development programme on the instructional digital learning training. The study demonstrated that the teachers increased in ICT proficiencies but this was limited to their own professional development and not so much of classroom implementation of ICT which results when transfer of learning takes place from training to practice. The study reported that teachers faced a complex mix of factors that when combined, contributed to challenges in transferring the ideas gained in the training programme to the classroom situation. It was evident from the findings that more systematic efforts are needed at the school levels and at the level of stakeholders who implement in-service teachers’ professional development programmes to move the goal of transforming teaching and learning through ICT-based innovations. Based on the outcomes, the study discussed recommendations to help smoothen the transition from teacher professional development programmes to actual classroom implementations in Ghanaian senior high schools and such similar contexts.
Keywords: ⛔ No DOI found

Examining mathematical task and pedagogical usability of web contents authored by prospective mathematics teachers - Akayuure, Peter; Apawu, Jones (International Journal of Research in Education and Science, 2015)
The study was designed to engage prospective mathematics teachers in creating web learning modules. The aim was to examine the mathematical task and perceived pedagogical usability of the modules for mathematics instructions in Ghana. The study took place at University of Education, Winneba. Classes of 172 prospective mathematics teachers working in design groups were involved in the study. Data were collected using Mathematical Task Usability Scale and Pedagogical Usability Rubrics. The result indicated 77.8% of the task contents examined contained worthwhile mathematical tasks. Descriptive analysis of data reflected three distinct categories of perceived pedagogical usability. Approximately 6%, 58% and 36% of the modules contained low, moderate and high pedagogical usability attributes. The study concluded that majority of the modules developed by the prospective teachers have considerable instructional value. Implications for involvement of prospective mathematics teachers in authoring web resources were discussed against the backdrop of policy initiatives for integrating emerging technologies.
Keywords: ERIC, Current Index to Journals in Education (CIJE); Electronic Publishing; Foreign Countries; Ghana; Higher Education; Instructional Material Evaluation; Learning Modules; Mathematics Activities; Postsecondary Education; Preservice Teachers; Rating Scales; Scoring Rubrics; Statistical Analysis; Student Developed Materials; Usability; Web Based Instruction; __:import:01; __:match:final; __:matched; __:study_id:2098955; __finaldtb

A design based research framework for implementing a transnational mobile and blended learning solution - Palalas, Agnieszka; Berezin, Nicole; Gunawardena, Charlotte; Kramer, Gretchen (International Journal of Mobile and Blended Learning (IJMBL), 2015)
The article proposes a modified Design-Based Research (DBR) framework which accommodates the various socio-cultural factors that emerged in the longitudinal PA-HELP research study at Central University College (CUC) in Ghana, Africa. A transnational team of stakeholders from Ghana, Canada, and the USA collaborated on the development, implementation, and subsequent modification of the DBR framework. The recommended framework is a result of lessons learned during this project in Ghana and as such, it is shaped by the need to be responsive to the local cultural and contextual contingencies. The article offers practical recommendations on the implementation of a mobile learning project in a cross-cultural setting, and provides a discussion of the salient cultural factors and the corresponding culturally-sensitive adaptations needed in the design research process. The Cross-Culture Design-Based Research (CC-DBR) framework is proposed to inform future transcultural m-learning studies.

Connecting africa using the TV white spaces: from research to real world deployments - Roberts, Sidney; Garnett, Paul; Chandra, Ranveer (2015 IEEE International Workshop on Local and Metropolitan Area Networks (LANMAN), 2015)
More than 4 billion people are not connected to the Internet. This is either because there is no infrastructure or because Internet access is not affordable. This digital divide is extreme in Africa. At Microsoft, we have been investigating various technologies to bridge this divide. In this paper we describe our research around the TV White Spaces, and how we have leveraged it, and worked with our partners to connect communities in Kenya, Tanzania, Ghana, Botswana, Namibia and South Africa.

Promoting teaching and learning in Ghanaian Basic Schools through ICT - Natia, James; Al-hassan, Seidu (International Journal of Education and Development using ICT, 2015)
The Basic School Computerization policy was created in 2011 to introduce computers and e-learning into the entire educational system to promote training and life-long learning. Using data obtained by Connect for Change Education Ghana Alliance, this paper investigates the extent to which school administration, and teaching and learning are promoted through the use of ICT in Ghanaian Basic Schools. The data was obtained through a cross-sectional survey involving a random sampling of 333 Primary and 295 Junior High Schools across four regions (Northern, Upper East, Upper West and Volta) in...
Keywords: ___working_potential_duplicate; ⛔ No DOI found